Interpretasi Satuan Litologi, Satuan Bentuk Lahan, Dan Struktur Geologi Dengan Integrasi Citra Srtm Di Wilayah Kota Bengkulu - Nofirman Nofirman (Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 2016)
Sumatra Island is geologically located above the zone plate subduction plate Indian Ocean and Australia. Subduction condition produces a trough system, melange, face basin arc, the folds and pataran, volcanoes and so forth. Expression subduction system is clearly visible on the city of Bengkulu, which is observed through lithologic unit, the unit of origin landform and geological structure. Based on the results of visual observation on the image of DEM from SRTM mapped lithologic unit located in the city of Bengkulu in the form of (1) the railroad alluvium, (2) alluvium, (3) sediment swamp, (4) limestone reefs, (5) the formation bintunan and (5) andesite. Mapping unit produces original landforms (a) landform volcanic origin, (b) structural landforms origin, (c) landforms denundasi origin, (d) landforms fluviatil origin, (e) landforms marine origin. Conditions geological structures located in the city of Bengkulu can not be done with careful and precise, so that the condition of the structure in the form of folds and faults as observed in the field have not seen adequately.